Determinant Factors of Completeness of Medical Resume Filling by Doctors at Pesawaran Regional General Hospital - Farista, Achmad Deza; Karyus, Aila; Djamaluddin, Abikusno (UI Scholars Hub, 2025)
A medical resume serves as a vital document that compiles essential information related to a patient’s clinical management. In 2019, the completeness rate of medical resume documentation at Pesawaran Regional General Hospital was only 37.4%. This study aimed to identify factors influencing the completeness of medical resume documentation by doctors through a quantitative, cross-sectional design involving 37 inpatient care doctors. Data were collected via questionnaires and direct observation, then analyzed using univariate, bivariate (Chi-Square), and multivariate (Logistic Regression) methods. Observation showed that 56.8% of medical resumes were incomplete. Questionnaire results indicated that 54.1% of respondents had negative perceptions of Standard Operating Procedures (SOP), 51.4% had high motivation, 62.2% perceived low rewards, 59.5% experienced democratic leadership, and 54.1% faced inadequate supervision. Bivariate analysis found significant associations between completeness and perceptions of SOP (p-value = 0.006; OR = 9.6), motivation (p-value = 0.029; OR = 6.0), leadership style (p-value = 0.044; OR = 5.8), and supervision (p-value = 0.001; OR = 18.4), while no significant association was found with perceived rewards (p-value = 0.760). Multivariate analysis identified supervision as the most dominant factor (OR = 39.281). These findings suggest that strengthening supervisory mechanisms and improving SOP clarity and implementation are essential for enhancing documentation completeness. Hospital management is advised to establish regular, structured supervision and continuous SOP review to ensure consistent compliance among doctors.